2018
DOI: 10.1188/18.cjon.142-145
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner Fellowship: Developing a Program to Address Gaps in Practice

Abstract: Formal training is an important mechanism to assist the new generation of nurse practitioners (NPs) entering the complex field of oncology. The growing number of patients with cancer and the expansion of treatment options demand structured oncology training to support the transition of novice advanced practice nurses to the field. Oncology NP fellowships are a potential solution for those seeking training centered on the management of patients with cancer. This article discusses the process of implementing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Many APPs enter oncology with limited specialty training. 17 This study confirmed these substantial gaps in hematology subspecialty education for APPs. The majority of the surveyed APPs reported that the small amount of hematology training they received in school did not adequately prepare them to practice with full confidence.…”
Section: Discussionsupporting
confidence: 74%
“…Many APPs enter oncology with limited specialty training. 17 This study confirmed these substantial gaps in hematology subspecialty education for APPs. The majority of the surveyed APPs reported that the small amount of hematology training they received in school did not adequately prepare them to practice with full confidence.…”
Section: Discussionsupporting
confidence: 74%
“…While NPs are noted to deliver cost-effective, high-quality medical care that addresses the need for medical providers, graduate education often lacks specialized postgraduate fellowships, resulting in the acquisition of on-the-job training. [26] With emerging research highlighting the need for NP fellowships across US specialty disciplines, Kesten and El-Banna [27] found that over 90% of program directors state an increase in NP recruitment and retention following NP fellowship implementation. Additionally, the majority of decision-makers favor NP fellowship implementation with few to no barriers and 84% of physician and administrative support and favor fellowship/residency acquisition.…”
Section: The Importance Of Np Fellowships In the Usmentioning
confidence: 99%
“…[28] In terms of admission requirements, 79.4% of the 68 NP postgraduate programs required a state NP license, 67.7% required a disciplinespecific certificate, 51.5% targeted new graduates, 22.1% required additional certification specific to the program, 51.5% required an NP specific degree such as pediatric or family NP, and 17.7% required a Drug Enforcement Agency number (DEA). [28] Performance and effect of increased ability, patient satisfaction, and quality of care are further evaluated in detail by Hoff et al [8] , Kesten and El-Banna, [27] Sciacca and Reville, [13] and Spetz et al [7] Examples of recent specialty NP fellowships successfully implemented within the last five years are depicted in Table I, in the fields of oncology, [26] palliative care, [29] emergency medicine, [30] and neurology. [31] Predominant NP fellowship and residencies offered throughout the US to date are distributed disparately throughout each state, where some states do not offer any NP fellowship programs whatsoever.…”
Section: Np Fellowships and Residencies In Specialties -What Is Known?mentioning
confidence: 99%
“…Specifically, in the advanced practice nurse setting, graduate-level education is focused mainly on primary care. One such program is the Oncology Nurse Practitioner Fellowship at the University of Miami Sylvester Comprehensive Cancer Center (Alencar, Butler, MacIntyre, & Wempe, 2018). They offer a blood and marrow transplant with cellular therapy training that spans 50 weeks.…”
Section: Advanced Education Opportunitiesmentioning
confidence: 99%